AN ANALYSIS OF TEACHER STRATEGIES IN TEACHING READING COMPREHENSION OF CLASS VII STUDENTS IN SMPN 12 DENPASAR - Ni Gede Diah Sutrisnawati; Putra, I Dewa Gede Rat Dwiyana; Suhardiana, I Putu Andre (Yavana Bhasha : Journal of English Language Education, 2026)
The aims of this study is to find out what strategies are used in teaching reading comprehension and analyze the strenghts and weakness of the strategy at SMPN 12 Denpasar, focusing on Class VII Students. This research used observation, interview, and content analysis to obtain data. The data was analyzed by using data reduction techniques, data display, and conclusion drawing/verification. The researcher found that the teachers employ knowledge activation, prediction, vocabulary, and games. Although there is a lack of time and unequal involvement, these tactics boost student motivation and preparedness. While reading, understanding key concepts and particular details is aided by skimming, scanning, and peer discussion. The drawbacks include inconsistent supervision and certain passive students. Q&A and games improve understanding and reflection. The drawbacks include little time for introspection and a narrow range of activities. Although more involvement and time management were required, the teacher's approach of combining cognitive, metacognitive, and social/affective tactics was generally successful.